Hyponormality of Toeplitz operators on Newton spaces: Hyponormality of Toeplitz operators on Newton spaces - Ko, Eungil; Lee, Ji Eun; Lee, Jongrak (Annals of functional analysis, 2025)
In this paper, we investigate properties of hyponormal Toeplitz operators whose symbols are analytic or co-analytic on a Newton space. We establish both necessary and sufficient conditions for a Toeplitz operator T φ to be hyponormal or normal. Additionally, we give some applications of such results.